Women's cosmetics in billboard ads a critical discourse-social semiotic analysis - Lazaro, Sigma Liberty G.; Teodosio, Sharon Fiel R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2006)
With the rise of billboards along the roads of EDSA, outdoor advertising is undeniably as important as the other traditional media like the television, radio, and print. Digital technology makes it possible for the production of billboards for cosmetics to be more realistic. This study analyzes billboards of cosmetics for women to show how billboard advertisements promote social acceptability and desirability for women, which are used to persuade women viewers to buy the products. Incorporating Fairclough's Critical Discourse Analysis and Kress and van Leeuwen's social semiotics in the analysis of billboard ads of cosmetics for women, the texts' features are described, their production and consumption are interpreted, and the power and ideology they exhibit are explained. The study reveals that billboards consistently depict an image of desirable woman that follows the western ideal - with perfectly white skin, long, shiny black hair, fresh breath, white underarms, and long polished fingernails. In so doing, billboards favor, create and prescribe standards to women consumers who accept these ideals without question. Women feel ashamed about their selves and feel the need to emulate the "made-up" and "artificial" images of "desirable" women on billboards by consuming the advertised cosmetics. In return, this makes marketers and advertisers gain more profit but women become more discontented.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.